A taxonomic revision of Angraecum section Dolabrifolia (Orchidaceae, Angraecinae), with the description of a new species from Gabon - Simo-Droissart, Murielle; Sonké, Bonaventure; Droissart, Vincent; Geerinck, Daniel; Lowry Ii, Porter P.; Stévart, Tariq (Phytotaxa, 2016)
Despite a paucity of material available from continental Africa, previous morphological and molecular phylogenetic studies have suggested that Angraecum, the largest genus of the angraecoid orchids, is polyphyletic. A recent study based on broad sampling from the region confirmed the monophyly of section Dolabrifolia and a clear delimitation of four of its five members, one of which represents a new species. Based on these results, a comprehensive taxonomic revision of Angraecum sect. Dolabrifolia is presented here. It includes an identification key and a detailed description of each species, along with color photographs, distribution maps, information on habitat and phenology, and a preliminary risk of extinction assessment according to the IUCN Red List categories and criteria. Species richness in the section is highest in Atlantic Central Africa and around the Albertine Rift. The new species, A. biteaui, is described and illustrated with line drawings. It most closely resembles A. aporoides in general aspect but differs in both foliar and floral characters, and is only known from lowland forests in Gabon.